Mariponasa: Transforming butterfly larval feces into biofertilizer (CIENCIA Y TECNOLOGÍA AGROPECUARIA, 2025)
Biofertilizers made from animal manure represent a sustainable and environmentally friendly alternative to conventional chemical fertilizers. This practice enables the utilization of animal by-products to enhance soil fertility. In addition to supplying essential nutrients, these biofertilizers promote beneficial microbial activity, which helps improve soil structure and optimize nutrient availability for plants. In this regard, it was considered to analyse the feces of four species of butterfly larvae, namely: Battus polydomas, Metemorpha elissa, Methona confusa, Hamadryas, to determine whether they can be considered as organic manure or biofertilizer. The microbiota of the samples of mariponase were also characterized, these were sown in selective and nutritive medium PCA, Agar Czapek and Agar Mac Conkey, also subjected to biochemical tests SIM, TSI and LYSINE, in addition, Gram staining was performed to identify and characterize the microorganisms present. The results showed high concentrations of aerobic mesophiles and a notable presence of nitrifying bacteria and enterobacteria, with Enterobacter cloacae and Klebsiella pneumoniae identified as the predominant species, Gram staining confirmed the presence of Gram-negative bacilli.
Keywords: Organic fertilization; entomofauna; butterflies